Household Economic Inequality in Australia - La Cava, G; La Cava, Gianni; Stone, Tahlee; Dollman, Rosetta; Kaplan, Greg (Reserve Bank of Australia, 2015)
We document some new stylised facts about consumption and income inequality (or ‘economic inequality’) among households in Australia. Based on household-level information from the Household Expenditure Survey we find that consumption inequality is lower on average than income inequality, but that income and consumption inequality have both increased a little since the early 1990s, with income inequality increasing by more. These findings are broadly similar to the changes in income and consumption inequality documented in other developed economies. We provide insight into the welfare implications of these changes using panel data from the Household, Income and Labour Dynamics in Australia Survey. We decompose the broad trends in income inequality into four statistical components: (i) changes in observed household characteristics; (ii) changes in the returns to unobserved skills; (iii) changes in the size of persistent income shocks (reflecting events such as promotions and long-term unemployment); and (iv) changes in the size of transitory income shocks (reflecting events such as bonuses, short-term unemployment and short-term illness). The reported trends in income inequality do not appear to be due to changes in observed household characteristics, but rather to changes in the size of persistent and transitory income shocks. Since the middle of the 2000s, at least some of the increase in income inequality has been due to persistent factors, a conclusion that is consistent with the rise in consumption inequality over the corresponding period.
Research Discussion Papers
Keywords: Finance -- Income (Salary and Wages); Housing -- Rental; Culture -- Inequality; Income, wealth and finances; Culture; Housing; Finance; Income (Salary and Wages); Rental; Inequality; Income, wealth and finances